Indonesia's Fiscal Policy in the Midst of Recession and Post-Pandemic Recovery Reviewed from an Islamic Fiscal Perspective - Fauzan Romadhian Khairi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The economic recession and public welfare challenges during 2020-2024 required Indonesia to implement comprehensive fiscal strategies to stabilize the economy and support recovery. This study evaluates Indonesia’s fiscal policies from the perspective of Islamic fiscal principles. Using a qualitative-descriptive approach, the research examines Indonesia’s fiscal policies, focusing on state revenue, spending, and deficit management. These policies are compared with Islamic fiscal principles derived from classical Islamic governance and the thoughts of modern Muslim economists. Indonesia’s fiscal policies align with Islamic principles in key areas, such as countercyclical spending to support public welfare and economic recovery, including allocations for health, social protection, and MSME support. However, significant gaps exist in revenue generation and deficit financing. While Indonesia relied on taxation and interest-based loans, Islamic fiscal principles advocate redistributive tools like zakat and sharia-compliant financing mechanisms, such as Sukuk. The findings highlight Indonesia’s partial alignment with Islamic fiscal principles, particularly in prioritizing welfare spending. Yet, the absence of zakat and reliance on interest-bearing debt underscore the need for adopting Islamic fiscal instruments. Integrating such tools could enhance fiscal equity and sustainability while adhering to maqasid al-shari’ah principles. Indonesia’s fiscal policies during the economic recession and recovery reflect efforts to address economic challenges and prioritize public welfare. However, adopting Islamic fiscal instruments like zakat and sukuk could strengthen alignment with Islamic principles, fostering more equitable and sustainable economic resilience.Keywords: Fiscal policy, economic recession, economic recovery, Islamic fiscal principles, Indonesia.